Effect of Cesium Iodide (CsI) Concentration Variation on the Performance of MethylAmmonium Lead Iodide (MAPbI₃)-based Perovskite Solar Cells - Zaki, Shakahuddin; Dahlan, Dahyunir; Sadiqin, Siti Naqiyah; Umar, Akrajas Ali (Jurnal Ilmu Fisika, 2025)
The fabrication of MAPbI3 perovskite solar cell (PSC) devices with the modification of adding cesium iodide (CsI) into the PbI2 layer to enhance performance has been successfully carried out. The used synthesis method was a two-step spin coating with CsI concentration variations: without CsI (control), 2 mg/mL, 3 mg/mL, and 5 mg/mL. Characterization using UV-vis, FESEM, and XRD showed improved in optical properties, morphology, and crystal stability. The UV-Vis spectrum indicated an increase in absorption from 2.29 to 3.17 a.u after CsI addition. FESEM results revealed that a 3 mg/mL CsI concentration produced a uniform morphology, a more compact film layer, and clear grain boundaries compared to other concentrations. XRD analysis showed a 2θ peak shift of 0.04°, indicating changes in crystal lattice parameters and increased lattice density without altering MAPbI₃ crystallinity. The device with 3 mg/mL CsI achieved an open-circuit voltage (Voc) of 1.2 V, a short-circuit current density (Jsc) of 11.34 mA/cm², a fill factor (FF) of 0.65, a power conversion efficiency (PCE) of 2.8%. In conclusion, 3 mg/mL CsI successfully enhanced PSC performance, but performance declined to 5 mg/mL.